LATE NEUROSYPHILIS: TRENDS AND CHALLENGES. - Ivan Dimitrov; Ara Kaprelyan; Milena Gentcheva; Borislav Ivanov; Radoslav Georgiev; Tony Avramov; Yavor Entchev; Nadezhda Deleva (Peytchinski Publishing, 2015)
Background: Syphilis is not only a disease of historical importance. It has been recognized that nowadays, in the era of AIDS, it still remains a serious challenge. For the last two decades there has been a resumption of neurosyphilis cases. This has revived the interest in the diagnostic and therapeutic challenges that the disease presents to clinical practice and to healthcare systems. Material/Methods: We present the overall picture of newly registered cases of syphilis in Varna municipality between 2009 and 2013, and report a case of neurosyphilis diagnosed at the first clinic of neurological diseases of St. Marina University Hospital during this period. Results: For the 5-year period, newly registered cases of syphilis in Varna have shown a tendency towards a decrease. Patients were typically in the early stages of the disease, primary and secondary. Late manifestations dropped from 29 in 2009 to 0 in 2010, but increased again to 15 in 2013. Only 1 case of neurosyphilis was registered during the 5-year period, in 2013. Conclusions: Neurological syndromes observed in cases of late neurosyphilis, presenting in different clinical forms, require a broad spectrum of differential diagnoses. Attention in everyday clinical practice should be focused on these cases which, though rare, are of high medical and social importance. Clinical cases of late neurosyphilis are often atypical and the early consideration of serologic tests or even biopsy may be of critical importance.